Bi2O3/Bi nanocomposites confined by N-doped honeycomb-like porous carbon for high-rate and long-life lithium storage. (March 2021) - Liu, Hao; Yang, Mengmeng; Yi, Zao; Duan, Tao; Yao, Weitang
Highlights: The unique honeycomb-like porous structure of Bi2 O3 /Bi@NHPC was conveniently synthesized. Porous carbon matrix promotes Li-ion/electron transfer and capacitive contribution. High-rate performance and long life are simultaneously obtained on Bi2 O3 /Bi@NHPC electrode. Abstract: The volume changes of Bi2 O3 and Bi, which have a high theoretical gravimetric ca-pacity and high volumetric capacity, during alloying is the main challenge in the fabri-cation of high-performance Bi-based electrodes. In the present study, a simple chemical blowing method is adopted to embed Bi2 O3 and Bi nanoparticles generated by thermal decomposition and reduction in an N-doped honeycomb-like porous carbon matrix (Bi2 O3 /Bi@NHPC). In charge/discharge processes, the honeycomb-like porous carbon matrix effectively prevents the Bi2 O3 and Bi nanoparticles from pulverization triggered by volume changes and provides abundant channels for fast electron and Li-ion diffusion. When utilized for lithium storage, the electrode exhibits a high reversible specific capacity of 408 mAh g −1 after 1000 cycles at 1 A g −1 . Remarkably, it presents a superior rate capability of 258 mAh g −1 at 10 A g −1 and a decent cycle retention of 78 % at 5 A g −1 after 2000 cycles. The qualitative analysis results reveal that the excellent rate performance and rapid reaction kinetics of the as-prepared electrode are mainly derived from the high capacitive contribution induced by the honeycomb-like porous carbon matrix. The reported results demonstrate that Bi2 O3 /Bi@NHPC, which has a convenient preparation method, is a potential anode material for lithium-ion batteries. Graphical abstract: Image, graphical abstract